Book review: Kelly, Jr, V. C. and Thorsborne, M. (Eds) (2014). The Psychology of Emotion in Restorative Practice – How Affect Script Psychology Explains How and Why Restorative Practice Works. London: Jessica Kingsley Publishers, 272pp, ISBN 978-1-84905-974-9 - David Orr (Scottish Journal of Residential Child Care)
Intuitively, restorative practice seems like it should work. It feels like a good idea. However, in this age of evidence-based practice and rigorous evaluation, funders and sceptics need reassurance that something definitely does 'work'. From my own perspective, I have long wished to see restorative practice principles become more fully embedded in the youth and criminal justice systems in Scotland. Such principles seem to have real value and relevance in the context of residential child care and work with vulnerable children and young people too. Take Atkinson Secure Children's Home in Exeter as an example. Puffett (2013) describes how this institution witnessed an 87% reduction in restraint incidents over five years and less frequent recourse to the use of single separation following staff members' embrace of restorative principles. It became the first Children's Home to be awarded a Restorative Service Quality Mark (RSQM) by the Restorative Justice Council (RJC). This edited collection by Vernon Kelly and Margaret Thorsborne is therefore extremely timely because in The Psychology of Emotion in Restorative Practice, they begin to articulate a theory as to why restorative practice 'works', drawing heavily from Affect Script Psychology (ASP).